tPA-MMP-9 Axis Plays a Pivotal Role in Mobilization of Endothelial Progenitor Cells from Bone Marrow to Circulation and Ischemic Region for Angiogenesis - Steve Leu; Yuan-Ji Day; Cheuk-Kwan Sun; Hon-Kan Yip (Hindawi Limited, 2016)
We examined the role of tissue plasminogen activator- (tPA-) matrix metalloproteinase- (MMP-) 9 in mobilizing endothelial progenitor cells (EPCs) from bone marrow to circulation and critical limb ischemia (CLI) region. Male C57BL/6J mice having been irradiated were categorized into wild-type mice (WT) receiving WT bone marrow cell (BMC) transfusion (group 1), WT mice receiving MMP-9 knockout (MMP-9−/−) BMC (group 2), MMP-9−/− receiving MMP-9−/− BMC (group 3), and MMP-9−/− receiving WT BMC (group 4), each of which was subdivided into sham control (SC), CLI, SC-tPA, and CLI-tPA. In groups 1 and 4, by post-CLI 18 h and day 14, circulating EPC (C-kit+/CD31+, Sca-1+/KDR+) levels were highest in CLI-tPA subgroup. In groups 2 and 3, EPC levels did not differ among all subgroups. The EPC levels in bone marrow were higher in groups 2 and 3 than those in groups 1 and 4. By day 14, in animals with CLI, expression levels of proangiogenic factors (CXCR4, SDF-1α, and VEGF) showed similar trends as circulating EPC levels. Moreover, the number of infiltrated neutrophils and macrophages in quadriceps was higher in groups 1 and 4 than groups in 2 and 3. In conclusion, tPA-MMP-9 axis plays a crucial role in EPC mobilization and angiogenesis in experimental CLI.